Laramie 2.0: The Journey of a Queer Professor. (March 2017) - Teman, Eric D.
Through autoethnographic poetry, I take the reader on a journey through my experience of moving to Laramie, Wyoming, to become faculty at the University of Wyoming. As a gay male who is still haunted by the 1998 brutal murder of Matthew Shepard in Laramie, I engage in storytelling: relaying my personal experiences of living in modern-day Laramie, showing the reader my fears, obstacles, and revelations through prose.